2000
DOI: 10.4049/jimmunol.164.6.3353
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activation of NF-κB in the Antrum of the Human Stomach

Abstract: Both in vitro studies and experiments in mice suggest a key role for transcription factor NF-κB as a mediator of mucosal inflammation. Experiments in vitro show that NF-κB activation may be a critical event in the production of proinflammatory molecules in Helicobacter pylori-associated gastritis. This study examines the expression and activity of NF-κB in situ in antral biopsies of 69 consecutive patients with immunohistochemical techniques. In the uninflamed stomach, NF-κB was highly expressed and active in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 36 publications
6
42
0
2
Order By: Relevance
“…The mechanisms and signaling pathways involved in H. pylori induction of NF-B responses in human GECs have been studied in great detail in vitro, yet the in vivo relevance of these observations has only rarely been investigated. Activated NF-B complexes were detected by immunohistochemistry within the gastric mucosa of individuals chronically infected with H. pylori (17,18,46). Consistent with the work presented here (Fig.…”
Section: Vol 76 2008 Helicobacter-induced Nf-b Activation In Mice 557supporting
confidence: 88%
See 1 more Smart Citation
“…The mechanisms and signaling pathways involved in H. pylori induction of NF-B responses in human GECs have been studied in great detail in vitro, yet the in vivo relevance of these observations has only rarely been investigated. Activated NF-B complexes were detected by immunohistochemistry within the gastric mucosa of individuals chronically infected with H. pylori (17,18,46). Consistent with the work presented here (Fig.…”
Section: Vol 76 2008 Helicobacter-induced Nf-b Activation In Mice 557supporting
confidence: 88%
“…pylori has been shown to up-regulate the expression of the transcription factor nuclear factor B (NF-B) in gastric epithelial cells (GECs) in vitro (21), as well as during chronic infection in humans (17,46). NF-B is a key regulator of proinflammatory responses in host cells (15).…”
mentioning
confidence: 99%
“…The same anti active NF-kB antibody has been used to perform immunohistochemistry in formalin ®xed, para n embedded tissue in other studies including several that have shown activated NF-kB in macrophages (Gaweco et al, 2000;Rogler et al, 1998). We ourselves have previously shown the speci®city of this antibody under the same conditions by showing colocalisation of TNFa, TRAF-2 and total NF-kB staining with the active NF-kB staining and showing clear nuclear localisation of the active NF-kB (van Den Brink et al, 2000). Phosphospeci®c antibodies are also increasingly being used in immunohistochemistry in formalin ®xed, para n embedded tissue, especially pJNK and pp38 MAPK (Omori et al, 2000;Pirvola et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Helicobacter pylori-associated gastritis is also marked by increased NF-κB activity in gastric epithelial cells (38). The number of NF-κB positive cells correlates with the degree of gastritis.…”
Section: Nf-κb Activation In Human Inflammatory Diseasesmentioning
confidence: 99%